From Cognition To Spirituality: A Comparative Study Of James J. Gross And Abdallah's Concept Of Emotion Regulation - Sabni, Ludfia; Tuzaroh, Fatimah; Yuwono, Adhimas Alifian (Universitas Muhammadiyah Tangerang, 2025)
This research discusses the comparison of the concept of emotion regulation according to James J. Gross from the perspective of cognitive psychology and Abdallah Rothman from the perspective of Islamic psychology based on spirituality. Emotion regulation is an important ability in maintaining mental health and quality of life, which in Western psychology is understood as a cognitive and behavioral process, while in Islamic psychology it is associated with spiritual and religious dimensions. This study uses a comparative qualitative approach with the method of literature study and content analysis of the main works of both figures, namely Handbook of Emotion Regulation and Developing a Model of Islamic Psychology and Psychotherapy. The results show that Gross emphasizes cognitive strategies such as cognitive reappraisal and expressive suppression to adaptively manage emotions, while Rothman places the qalb at the center of emotion regulation and emphasizes spiritual practices such as tawbah, dhikr, and tawakal. Both approaches have similarities in the goal of achieving well-being, but differ in the basic paradigms and strategies used. The integration of these two paradigms offers a more holistic and applicable understanding of emotion management, especially in a multicultural and religious society like Indonesia.